2012
DOI: 10.1111/j.1467-9922.2012.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

L2 Negation Constructions at Work

Abstract: This article explores the usage‐ and exemplar‐based roots of second language (L2) negation construction learning. Based on two longitudinal case studies involving two adult L2 English learners and a corpus of 63 three‐hour sessions of recorded classroom interactions, the study shows that L2 learning follows the predictions of usage‐based models of language knowledge and acquisition, as the two participants’ learning of English negation constructions is found to go from recurring expressions toward an increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
103
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 44 publications
10
103
0
6
Order By: Relevance
“…As an issue this is outside the scope of the current article. However, recent developments in the CA-SLA literature provide evidence of adult L2 speakers' longitudinal development of general interactional competencies (Kasper & Wagner, 2011), specific competencies in syntactic structures through comparisons of the two languages (e.g., Eskildsen, 2012;Hauser, 2013;Ishida, 2009), and the development of recipient design (Nguyen, 2012). Downloaded by [New York University] at 01:47 08 June 2015 FILIPI In describing the process of second language learning, Eskildsen (2011, p. 332) states that "language learning is emergent, constant, and never-ending."…”
Section: Discussionmentioning
confidence: 98%
“…As an issue this is outside the scope of the current article. However, recent developments in the CA-SLA literature provide evidence of adult L2 speakers' longitudinal development of general interactional competencies (Kasper & Wagner, 2011), specific competencies in syntactic structures through comparisons of the two languages (e.g., Eskildsen, 2012;Hauser, 2013;Ishida, 2009), and the development of recipient design (Nguyen, 2012). Downloaded by [New York University] at 01:47 08 June 2015 FILIPI In describing the process of second language learning, Eskildsen (2011, p. 332) states that "language learning is emergent, constant, and never-ending."…”
Section: Discussionmentioning
confidence: 98%
“…Questions pertaining to this process are typically investigated in terms of a priori constructions, e.g. locative motion constructions and object transfer constructions (Ellis and Ferreira-Junior 2009;Year and Gordon 2009), can-constructions (Eskildsen, 2009), auxiliary do-constructions (Eskildsen 2011); negation constructions (Eskildsen and Cadierno 2007;Eskildsen 2012), motion constructions (Li 2014;Li, Eskildsen, and Cadierno 2014;Eskildsen, Cadierno, and Li this volume; for a recent overview, see Cadierno forthc. ), relative clauses (Mellow 2006), question formation (McDonough and Kim 2009;Eskildsen 2015), French c'est and Swedish det är constructions (Bartning and Hammarberg 2007), German gehen and fahren (Roehr-Brackin 2014), and constructions based around the use of es que in L2 Spanish (Yuldashev, Fernandez, and Thorne 2013).…”
Section: Cub-slamentioning
confidence: 99%
“…In the recent study, the importance of learning formulaic sequences was acknowledged (Ellis, 2008(Ellis, , 2012Ellis & Larsen-Freeman, 2009;Myles & Cordier, 2017). Eskildsen (2012) reported that the frequency of FS English negation patterns among Spanish adult learners demonstrated an effect on English learning. Kidd, Lieven, and Tomasello (2010) found that children's (at age 6) repetition of the target sentence in L2 learning depended on the higher frequency input used by the teacher.…”
Section: Formulaic Sequencesmentioning
confidence: 99%